(untitled) (Research, Society and Development, 2021)
The use of alternative mortars in civil construction is currently an important tool to make the sector sustainable and contribute to the management of solid waste generated by the exploration and sale of ornamental stones. In this context, this study analyzed the influence of partial replacement of Portland cement by expanded and ground perlite on the simple compressive strength of mortars made with aggregate from quartzite waste. To this end, the physical, chemical and mineralogical characterization of the materials used and the mechanical performance of the studied mortars were carried out. The granulometry of the quartzite residues and the simple compressive strength of the investigated mortars were determined for the trace determined in the mixture design. The results showed that the partial replacement proposed in this research is viable. After the graphic analysis and the coefficients of variation obtained for the simple compression strength values, it was concluded that the hypothesis raised contributes to making the civil construction sector sustainable as there was a positive effect for the adopted replacement content.